2016
DOI: 10.4172/2157-7471.1000348
|View full text |Cite
|
Sign up to set email alerts
|

Soluble material secreted from Penicillium chrysogenum isolate exhibits antifungal activity against Cryphonectria parasitica- the causative agent of the American Chestnut Blight

Abstract: The American chestnut (Castanea dentata) was once the dominant canopy tree along the eastern region of the United States. Cryphonectria parasitica, the causative agent of chestnut blight, was introduced from Asia in the early 1900's, and obliterated the chestnut population within 50 years. We sought to identify environmental microbes capable of producing factors that were fungicidal or inhibited growth of C. parasitica in the hopes developing a biological control of chestnut blight. We isolated a filamentous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…against fungal plant pathogens. Florjanczyk et al [45] demonstrated that extracellular fractions from P. chrysogenum had inhibited the growth of Cryphonectria parasitica, the causative agent of blight on American chestnut (Castanea dentata). The current findings suggest that the antifungal activity of the cell-free culture filtrates from 30 days old Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…against fungal plant pathogens. Florjanczyk et al [45] demonstrated that extracellular fractions from P. chrysogenum had inhibited the growth of Cryphonectria parasitica, the causative agent of blight on American chestnut (Castanea dentata). The current findings suggest that the antifungal activity of the cell-free culture filtrates from 30 days old Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Cryphonectria parasitica, is an ascomycota fungi which can form dicarion when hold together fungal colonies and hyphae of different populations (Marra and Milgroom, 2001;Florjanczyk, Barnes, Kenneyand & Horzempa, 2006). Branches of chestnut trees produce spores that spread to other trees by wind (Marra et al, 2001;Florjanczyk et al, 2016). Spores enter to open wounds in root tissue and the fungus growth goes along with oxalic acid (OA) release.…”
Section: Introductionmentioning
confidence: 99%
“…Spores enter to open wounds in root tissue and the fungus growth goes along with oxalic acid (OA) release. This causes a decrease in pH of chestnut tissue (Zhang, 2013;Florjanczyk et al, 2016). Decreased pH levels, at the same time inhibits the function of chestnut tissue and this causes cancer genesis (Zhang, 2013;Chen, Sun, Narayanan, Nuss & Herzberg, 2010;Florjanczyk et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations